ASUPAN LEMAK DAN SERAT DENGAN KADAR TRIGLISERIDA PADA PASIEN DIABETES MELLITUS TIPE II - Apriyani, Fitri (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
Diabetes mellitus is a disease that can be prevented by lifestyle changes such efforts diet. Where should limit your intake of fat and fiber intake multiply. The purpose of this study was to determine the relationship of fat and fiber intake with triglyceride levels in patients with diabetes mellitus type II in Internal Medicine Poly General Hospital Dr. M. Yunus Bengkulu. The method used in the case-control study using a retrospective approach. Sampling was purposive sampling by the sampling is done by taking the patient or respondent in accordance with the specified criteria researchers. Univariate analysis using statistical methods and analysis using the Bivariate Correlation. The results showed that there was significant correlation with p = 0.002> 0.05, the variable fat intake with triglyceride levels in patients diabetes mellitus type II in Internal Medicine Poly General Hospital Dr M Yunus Bengkulu, and no significant relationship with the variable fiber intake with triglyceride levels of p = 0.183> 0.05 in patients diabetes mellitus type II in Internal Medicine Poly General Hospital Dr M Yunus Bengkulu.